Thermodynamic and computational studies of Promethazine hydrochloride drug in aqueous and aqueous Choline-based deep eutectic solutions - Ankita S. Chandak; Ritesh Motghare; Ratiram G. Chaudhary; Sangesh P. Zodape (Journal of Ionic Liquids)
This study explores deep eutectic solvents (DESs) as environmentally friendly green solvents with potential applications in the formulation of drug delivery systems (DDSs). By focusing on the important aspect of optimizing molecular interactions between drugs and DESs, this work offers thermodynamic and molecular interaction insights that facilitate the strategic selection of suitable solvents for advanced medicinal applications. In this regard, the density(ρ) and sound velocity (u) of the drug Promethazine hydrochloride (P.HCl) in aqueous and aqueous 0.5/ 1.0 mol.kg−1 DES (ChCl:U) solutions were measured across various temperatures (288.18–318.15 at 5 K interval). The thermodynamic and compressibility properties such as apparent molar volume of solute (Vϕ), limiting apparent molar volume of solute (Vϕ0) apparent molar compressibility of solute (KS,ϕ), limiting apparent molar compressibility of solute (KS,ϕ0), isentropic compressibility of solution (κS), thermal expansion coefficient (α), apparent molar expansivity of solute (Eϕ) and limiting apparent molar expansivity of solute (Eϕ0) were computed from the experimental results. Additionally, the positive values of transfer parameters (ΔtrVϕ0) and (ΔtrKsϕ0) suggested the dominance of ionic-hydrophilic interactions. Further, positive Hepler's constant (∂2Vϕ0/∂T2) values represent structure-making ability of drug P.HCl in all the investigated systems. Also, DFT analysis by using Gaussian 09 at B3LYP/6–311+G(d,p) was used for geometry optimization, reactive site identification (3D-MEP), and charge distribution analysis (CHELPG) of P.HCl and ChCl:U systems. The experimental and computational results reveal strong attractive interactions between P.HCl and DES (ChCl:U) in aqueous solutions, emphasizing the potential of DES-based systems to improve P.HCl drug solubility and stability, thereby paving the way for advanced drug delivery technologies.